2017
DOI: 10.1038/s41522-017-0016-3
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus subtilis utilizes the DNA damage response to manage multicellular development

Abstract: Bacteria switch between free-living and a multicellular state, known as biofilms, in response to cellular and environmental cues. It is important to understand how these cues influence biofilm development as biofilms are not only ubiquitous in nature but are also causative agents of infectious diseases. It is often believed that any stress triggers biofilm formation as a means of bacterial protection. In this study, we propose a new mechanism for how cellular and environmental DNA damage may influence biofilm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 43 publications
1
43
0
Order By: Relevance
“…The existence of a front suggests that colony expansion rate is nutrient-limited [43], and that the ∼ 1 mm width of the matrix-producing region may be set by a nutrient penetration depth, D/q, where D is the nutrient diffusivity and q is the nutrient uptake rate [44]. The accumulation of metabolic by-products, such as reactive oxygen species [45], has been recently shown to lead to decreased matrix gene expression in developing biofilms. Thus, metabolic gradients and nutrient-depletion dynamics likely drive the transition from matrix production to sporulation during front propagation.…”
Section: Discussionmentioning
confidence: 99%
“…The existence of a front suggests that colony expansion rate is nutrient-limited [43], and that the ∼ 1 mm width of the matrix-producing region may be set by a nutrient penetration depth, D/q, where D is the nutrient diffusivity and q is the nutrient uptake rate [44]. The accumulation of metabolic by-products, such as reactive oxygen species [45], has been recently shown to lead to decreased matrix gene expression in developing biofilms. Thus, metabolic gradients and nutrient-depletion dynamics likely drive the transition from matrix production to sporulation during front propagation.…”
Section: Discussionmentioning
confidence: 99%
“…The reporter fusion was then moved into 3610 by transduction (40), generating strain JG156. To construct the dual-reporter, the reporter was introduced to YCN095, which contains a P tapA -mKate2 reporter fusion integrated at sacA (44), generating strain JG157.…”
Section: Methodsmentioning
confidence: 99%
“…We propose a potential mechanism for this activation: recent research has indicated that certain cells in a culture will tend to accumulate reactive oxygen species and DNA damage. Those cells will produce Sda (a developmental checkpoint protein), and form a subpopulation separate from those that produce biofilm 35 . The LexA+, biofilmpopulation would no longer be producing EpsE, which catalyzes a step in the biofilm synthesis process and also suppresses swarming 36 .…”
Section: I-modulons Generate Novel Hypotheses I-modulon Activities Cmentioning
confidence: 99%